The Evaluation Process of Industrial Class in Light Automotive Engineering Competencies - Mashudi, Ali; Khumaedi, Muhammad; Widjanarko, Dwi (Journal of Vocational and Career Education, 2021)
There was a technology gap between industry and vocational schools. The school curricula were not following industrial needs and the educators were lack of mastery of the latest technologies according to current industry needs. The study evaluated Mitsubishi's industrial class process on students, supervisors, business, and the industrial world (DU/DI). This research applied evaluation research with a descriptive quantitative approach. The students of XII Light Automotive Vehicle who participated in the Mitsubishi industrial class of SMK Bina Utama Kendal became the participants in this research. The research subject consisted of 34 students, ten industrial teachers, and two teachers from Mitsubishi. Then, the data instruments technique applied observation, questionnaires, and documentation. The validity test adopted Product-Moment, while the reliability test used Cronbach-Alpha. The data analysis technique applied a descriptive statistical test. The result showed Mitsubishi's industrial class process toward students was sufficient, while teachers and DU/DI were declared very high.